Supracondylar femoral extension osteotomy and patellar tendon advancement in the management of persistent crouch gait in cerebral palsy - Das, Sakti Prasad (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Severe crouch gait in adolescent cerebral palsy is a difficult problem to manage. The patients develop loading of patellofemoral joint, leading to pain, gait deviation, excessive energy expenditure and progressive loss of function. Patella alta and avulsion of patella are the other complications. Different treatment options have been described in the literature to deal with this difficult problem. We evaluated outcome of supracondylar femoral extension osteotomy (SCFEO) and patellar tendon advancement (PTA) in the treatment of crouch gait in patients with cerebral palsy. MATERIALS AND METHODS: Fourteen adolescents with crouch gait were operated by SCFEO and PTA. All subjects were evaluated pre and postoperatively. Clinical, radiographic, observational gait analysis and functional measures were included to assess the changes in knee function. RESULTS: Cases were followed up to 3 years. The patients walked with increased knee extension and improvement in quadriceps muscle strength. Knee pain was decreased and improvements in functional mobility and radiologic improvement were found. CONCLUSION: SCFEO and PTA for adolescent crouch gait is effective in improving knee extensor strength, reducing knee pain and improving function.